Fixation for metaphyseal-diaphyseal junction noncomminuted fracture of the distal humerus in children: K-wire or ESIN, how to decide? - Li, Minglei; Liu, Tianjing; Li, Qiwei; Li, Lianyong; Zhang, Lijun; Shi, Liwei; Wang, Enbo (Frontiers in Pediatrics, 2025)
BackgroundThe metaphyseal-diaphyseal junction (MDJ) fracture of the distal humerus has posed significant difficulty clinically, as the increased height of the distal fragmant makes it hard for Kirschner wires to reach the proximal fragment. Our previous study provided suggestions for the choice of fixation in metaphyseal-diaphyseal junction (MDJ) fracture of the distal humerus according to the location of the fracture line based on biomechanical analysis. This study went on to testify an advanced suggestions in clinical patients.MethodsNormal elbow x-rays were measured to get a normal reference value to define the location of the fracture. A ratio of c' (the diameter of humeral shaft at the most proximal point of the fracture line)/d (the diameter of humeral shaft at distal humerus) was used to define the location of the fracture and guide the selection of fixation. According to our previous research, the ratio of c′/d was used to define the location of the fracture. Eighty-nine patients with MDJ fractures were included. For patients with high MDJ fracture elastic stable intramedullary nails (ESIN) were selected and for those with low MDJ fractures Kirschner wires were used. The short-term outcome was assessed using the Flynn criteria.ResultsThe c/d ratio of 1.2 was finally used to define the high or low location of the fracture. All the 89 MDJ fractures healed uneventfully. 73 of them were fixed with lateral or crossed pinning and 84.9% of them were ranked as excellent. 16 cases were fixed with ESIN and 81.3% were excellent. There were no significant difference between the outcomes of the groups.ConclusionsESINs were used for fractures in the higher part of the MDJ region, defined as c′/d < 1.2. Three lateral divergent or crossed pins were used for fractures in the lower part of the MDJ region with c′/d ≥ 1.2. This strategy, as recommended by our previous biomechanical research, has been demonstrated to be practical in clinical practice.Level of evidenceLevel III retrospective cohort study.